THE DOCTRINAIRE AUTHORITY: THE COURT OF JUSTICE OF THE EU AND THE FUNDAMENTAL RIGHTS - Ilik, Goran (The European Journal of Applied Economics, 2013)
This paper represents the analysis of the Court of Justice of the EU, in particular the Court of Justice, and its “interpretive power”, within its authority for diffusion and proliferation of the EU law. Namely, the paper describes the position, responsibilities, powers and the role of the Court of Justice, in order to penetrate into its institutional performances as doctrinaire authority, regarding the Charter of Fundamental Rights of the EU as its interpretive framework. Also, the paper presents the most representative axiological determinations of the EU as a basis of the “interpretive power” of the Court of Justice. Accordingly, the paper describes the Court as a central judicial EU institution that with its “interpretive power” generates legal doctrines through the prism of fundamental rights and freedoms. Consequently, the Court of Justice appears as undisputed doctrinaire authority that assumes the role of doctrine - maker and doctrine - keeper of the human rights and freedoms, accepted and promulgated by the EU.